2012
DOI: 10.1128/jvi.05411-11
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Entry via Somatostatin Receptors Using a Novel Modified Retrovirus Glycoprotein That Delivers Genes at Levels Comparable to Those of Wild-Type Viral Glycoproteins

Abstract: Here we report a novel viral glycoprotein created by replacing a natural receptor-binding sequence of the ecotropic Moloney murine leukemia virus envelope glycoprotein with the peptide ligand somatostatin. This new chimeric glycoprotein, which has been named the Sst receptor binding site (Sst-RBS), gives targeted transduction based on three criteria: (i) a gain of the use of a new entry receptor not used by any known virus; (ii) targeted entry at levels comparable to gene delivery by wild-type ecotropic Molone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 61 publications
1
29
1
Order By: Relevance
“…Only in two cases has efficient retargeting been achieved. Retargeting toward the somatostatin receptor resulted in the loss of the affinity for the wild-type mCAT-1 receptor, while using CXCR4 as the entry receptor was efficient only in a specific cell line (19,25). SL3-2 envelope protein, because of its limited and ecotropiclike tropism, offers another candidate for a retargeting scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only in two cases has efficient retargeting been achieved. Retargeting toward the somatostatin receptor resulted in the loss of the affinity for the wild-type mCAT-1 receptor, while using CXCR4 as the entry receptor was efficient only in a specific cell line (19,25). SL3-2 envelope protein, because of its limited and ecotropiclike tropism, offers another candidate for a retargeting scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Another intriguing possibility is that surface proteins must fulfill as-yet-undefined criteria for being able to mediate entry of a retrovirus. APJ is one of the coreceptors of HIV (11), and the other reported cases of efficient retargeting have been toward CXCR4 (25), another of the HIV coreceptors; somatostatin (19); and HuPAR-1 (22,23), all of them belonging to the GPCR family of proteins. The design of retargeted envelope proteins does not seem to be a case of simplified generic design but requires a case-by-case development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Li and colleagues have successfully replaced the receptor-binding domain of Mo-MLV with the ligand of the somatostatin receptor and by this inducing viral infection through the somatostatin receptor with titers equal to that of the wild-type virus (14). However, a later report showed that postbinding restrictions existed, depending on the somatostatin receptor used (15).…”
mentioning
confidence: 99%
“…Its parent glycoprotein initiates infection by binding to the ecotropic MLV receptor, mCAT-1 (mouse cationic amino acid transporter 1) (14-16), forming MLV-mCAT-1 complexes that are internalized (17). The modifications that created Sst-RBS resulted in a switch from use of mCAT-1 to the use of somatostatin receptors (13), a family of G protein-coupled receptors that are not entry receptors for any known virus and ordinarily recognize SST-14 and its peptide mimetics. SST-14 is an agonist to five somatostatin receptors (SSTR), subtypes 1 through 5, each encoded by a distinct gene (18).…”
mentioning
confidence: 99%